One-way surface states due to nonreciprocal light-line crossing. (10th June 2015) - Abbasi, Fereshteh; Davoyan, Arthur R; Engheta, Nader
Abstract: We revisit the problem of the surface plasmon polariton (SPP) propagation at a metal–magneto-optical dielectric interface and predict a conceptually different regime of one-way surface wave propagation. We show that in the presence of magnetization, the nonreciprocal crossing of the light-line by dispersion curve of SPPs is possible. This leads to the formation of leaky-wave surface states in one of the propagation directions, whereas in other direction SPPs are confined to the interface. We show that such a regime of surface plasmon propagation is fundamentally different from one-way regimes of surface waves predicted earlier.